ARECANUT AND BAMBOO BLENDED GREEN TEXTILES - A. PADMA, JOYSHREE AYEKPAM, D. ANITHA and (The Journal of Research, PJTSAU, 2017)
Environmental awareness, new rules and growing demand for healthier and environmentally friendly products are forcing researchers to put efforts and development activities. The urge to replace synthetic fiber with natural fiber is increasing. Natural fibers are available everywhere, and researchers are attracted towards them as promising alternative material to synthetic fibers due to their specific strength, low cost, renewability, market appeal, fullybiodegradable nature, and non-abrasive character (Jawaid and Khalil 2011).